Mental Health of Pediatric Patients Convalescent from COVID-19 in Cienfuegos - Yanara Calzada Urquiola; Laura Magda López Angulo; María Felicia Casanova González (Revista Finlay)
Foundation: children and adolescents constitute a particularly vulnerable group in times of pandemic, which is why it is necessary to detect risk situations arising from them that may compromise the mental health of this population. Objective: to characterize the mental health status present in pediatric patients’ convalescent from COVID-19 in Cienfuegos. Methods: an exploratory, cross-sectional study was carried out on 153 children and adolescents (3-18 years) who attended the provincial multidisciplinary consultation for convalescents from COVID-19 at the Paquito González Cueto University Pediatric Hospital in Cienfuegos. To obtain the information, a semi-structured interview, psychiatric examination and Abilities and Difficulties Questionnaire were used. The database and statistical processing were done through the SPSS system, version 21.0. Descriptive statistical tests were used. Results: children and adolescents recovering from COVID-19 are characterized by high levels of anxiety. It was the affective functions that were most affected by the psychiatric examination, represented in 29.4 % of the cases, followed by sleep and eating needs and habits (14.4 %). Anxiety disorder, adjustment disorder and sleep disorder were the main mental disorders diagnosed. Conclusion: the mental health of the child and youth population of a group of patient’s convalescents from COVID-19 has been affected, however, not all psychological responses can be classified as illnesses, because the majority are normal reactions to a situation abnormal.